Dynamics of Submicroscopic Plasmodium falciparum Infections Throughout Pregnancy: A Preconception Cohort Study in Benin. (12th September 2019) - Hounkonnou, Cornélia P A; Briand, Valérie; Fievet, Nadine; Accrombessi, Manfred; Yovo, Emmanuel; Mama, Atikatou; Sossou, Darius; Vianou, Bertin; Massougbodji, Achille; Ndam, Nicaise Tuikue; Cot, Michel; Cottrell, Gilles
Abstract: Background: In the context of global malaria elimination efforts, special attention is being paid to submicroscopic Plasmodium falciparum infections. In pregnant, sub-Saharan African women, such infections are more prevalent than microscopic infections, and are thought to have adverse effects on both mothers' and newborns' health. However, no study has studied the dynamics and determinants of these infections throughout pregnancy. Retard de Croissance Intra-uterin et Paludisme (RECIPAL), a preconception cohort study carried out in Benin between 2014 and 2017, represented a unique opportunity to assess this issue. Methods: We used data from 273 pregnant Beninese women who were followed-up from preconception to delivery. We studied the dynamics of and factors influencing submicroscopic (and microscopic) P. falciparum infections during the 3 trimesters of pregnancy, using an ordinal logistic mixed model. Results: The incidence rate of submicroscopic P. falciparum infections during pregnancy was 12.7 per 100 person-months (95% confidence interval [CI] 10.8–14.9), compared to 6.7 per 100 person-months (95% CI 5.5–8.1) for microscopic infections. The prevalences were highest in the first trimester for both submicroscopic and microscopic infections. After adjustment for potential confounding factors, we found that those of young age and those with a submicroscopic P. falciparum infection prior to pregnancy were at significantly higher risks of submicroscopic and microscopic infections throughout pregnancy, with a more pronounced effect in the first trimester of pregnancy. Conclusions: The first trimester of pregnancy is a particularly high-risk period for P. falciparum infection during pregnancy, especially for the youngest women. Malaria prevention tools covering the preconception period and early pregnancy are urgently needed to better protect pregnant women and their newborns. Abstract : In a preconception malaria cohort study, the prevalence of submicroscopic versus microscopic Plasmodium falciparum infections was higher throughout pregnancy, most markedly in the first trimester, and young women with submicroscopic infections before pregnancy had a higher subsequent risk of infection.